2017
DOI: 10.1037/rep0000132
|View full text |Cite
|
Sign up to set email alerts
|

Who self-identifies as disabled? An examination of impairment and contextual predictors.

Abstract: Stigma and severity were the strongest predictors of disability identification. Future work should examine ways to foster positive disability identity such as cross-impairment connections through support groups, mentoring, and collective action against stigma. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
83
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(92 citation statements)
references
References 61 publications
1
83
0
4
Order By: Relevance
“…Related to this, previous research indicated that there may be qualitative differences on how stigmatization is experienced among different minority groups, and even among people with different types of disabilities (e.g., Goffman, ; Olkin & Pledger, ). Nevertheless, the disabled group is suggested to share many commonalities with other minority groups in terms of perceiving stigma and oppression (Bogart, Rottenstein, Lund, & Bouchard, ), and thereby, we believe that findings may be replicated in different intergroup contexts.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Related to this, previous research indicated that there may be qualitative differences on how stigmatization is experienced among different minority groups, and even among people with different types of disabilities (e.g., Goffman, ; Olkin & Pledger, ). Nevertheless, the disabled group is suggested to share many commonalities with other minority groups in terms of perceiving stigma and oppression (Bogart, Rottenstein, Lund, & Bouchard, ), and thereby, we believe that findings may be replicated in different intergroup contexts.…”
Section: Discussionmentioning
confidence: 77%
“…However, research shows identification with support groups to lead physically impaired individuals to develop a healthier mental well-being (Wakefield, Bickley, & Sani, 2013) and the disability identity to directly relate to higher levels of collective and personal self-esteem (Nario-Redmond, Noel, & Fern, 2013). Especially according to the social model of disability, the disabled group shares many similarities with other minority groups such as ethnic/racial minorities (Bogart, Rottenstein, Lund, & Bouchard, 2017) and disability is a collective construct and a central aspect of identity, which is often an enriching and positive experience (Gill, 1997;Swain & French, 2000). Other research has shown that disability pride, a positive view of disability identity, may suppress the negative effects of stigma on self-esteem (Bogart, Rottenstein, & Lund, 2018).…”
mentioning
confidence: 99%
“…For PWD, group boundary permeability may be influenced by multiple factors, including impairment‐related characteristics. For example, if PWD have nonvisible or less disruptive impairments, they may be able to better approximate nondisabled group status, thereby avoiding pervasive stigma (Bogart, Rottenstein, Lund, & Bouchard, ). Likewise, if people can sufficiently remediate their impairment conditions through medical treatment (e.g., Fernández, Branscombe, Gómez, & Morales, ), or mitigate barriers to mainstream social exclusion through material means (e.g., money, technologies) they will be more likely to pursue individual coping strategies (Dirth & Branscombe, ).…”
Section: Perceiving Discrimination As Illegitimatementioning
confidence: 99%
“…Unfortunately, we did not have a measure of identification per se: For most of the study period, disability status was measured with a question, “Do you yourself have a disability?” However, Bogart et al. () demonstrated that experiential variables are related to identifying with the category of “PWD.” For example, identification is stronger if the person's disability is more noticeable, more severe, causes more pain, or if they have had the disability longer. The similarities between Bogart's measures and ours suggest that participants with disabilities that are difficult to hide, severe, and involve physical impairment may identify more strongly as a person with a disability.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that experiences that make an individual more likely to identify as a person with a disability may be associated with lower prejudice against PWD. Research by Bogart, Rottenstein, Lund, and Bouchard () has uncovered some experiential factors related to identification as a person with a disability, such as severity and duration of the disability. These variables, and others describing the precise nature and intensity of a disability, may therefore predict disability prejudice among people who themselves have disabilities.…”
Section: Introductionmentioning
confidence: 99%